Oral candida in HIV positive women: influence of oral hygiene, clinical and social factors on the carriage rates and the influence of virulence of the organism on the development of clinical infection - Owotade, Foluso John (My University, 2014)
Introduction Patients with HIV infection frequently encounter oral candidiasis, caused by Candida species. However, factors responsible for Candida colonisation and development of oral candidiasis in these patients are controversial. This study investigated the effect of social and clinical factors on oral Candida colonisation in HIV positive women. In addition, virulence of these organisms during clinical infection, the role of non-albicans Candida and reinfections with C. albicans were investigated.
Degree of Doctor of Philosophy in Medicine by research only A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy in Medicine. Johannesburg, 2014
Keywords: Candida; HIV-1 Infections